An Experimental Study to Evaluate the Anti-Diarrheal Activity of Bhuvaneshwara Rasa in Wistar Albino Rats - Simi Jose,; Chaitra L.V, (International Journal of Ayurveda and Pharma Research, 2021)
Atisara (Diarrhea) is most commonly encountered disease of the present era, due to unhealthy and irregular habits. Atisara (Diarrhea) finds a place as important disease in individual’s life as everyone suffers from it at least once in life time. Bhuvaneshwara rasa is a unique herbo-mineral formulation explained in Bhaishajya ratnavali indicated for all kinds of diarrhea cases. Bhuvaneshwara rasa is a potent formulation having Saindhava, Triphala, Yamani, Bilva peshika and Gruhadhooma.Materials and methods: Raw materials were screened and collected and the formulation selected for the present study Bhuvaneshwara rasa was prepared accordingly. Anti-diarrheal activity of Bhuvaneshwara rasa was evaluated experimentally in albino rats. Experimental study was conducted in 3 groups of animals for anti-diarrheal study each. Anti-diarrheal study was done by castor oil induced diarrhoea and castor oil induced enter-pooling method. Bhuvaneshwara rasa (test drug) and Loperamide are effective in controlling diarrheal episodes. Bhuvaneshwara rasa has shown significant Anti-diarrheal activity in both Castor oil -induced diarrhea and castor oil induced enteropooling, test drug effective than control.Result: Bhuvaneshwara rasa was prepared according to SOP. Test drug group have shown effect experimentally. Conclusion: Bhuvaneshwara rasa is a good anti-diarrheal drug. It can be administered in all types of Atisara.